The Vasculature within the Paraventricular Nucleus of the Hypothalamus in Mice Varies as a Function of Development, Subnuclear Location, and GABA Signaling - Frahm, K. A.; Schow, M. J.; Tobet, S. A. (Hormone and Metabolic Research, 2012)
The paraventricular nucleus of the hypothalamus (PVN) is a cell group that plays important roles in regulating sympathetic vasomotor tone, food intake, neuroendocrine and autonomic stress responses, and cardiovascular function. The developing PVN is surrounded by neuronal elements containing, and presumably secreting, gamma-aminobutyric acid (GABA). The vasculature of the adult PVN is notably denser than in other brain regions or in the PVN during perinatal development. To characterize the postnatal angiogenic process in mice, blood vessels were analyzed at P8, 20, and 50 in rostral, mid, and caudal divisions of the PVN in males and females. Vascular changes relative to disruption of the R1 subunit of the GABAB receptor were evaluated at P8 and P20. For defined regions of interest within the PVN there were age dependent increases in blood vessel lengths and branching from P8 to 20 to 50 with the most notable increases in the middle region. Loss of GABAB receptors did not influence vascular characteristics at P8 in any region, but by P20 there was significantly (20%) less blood vessel length and branching in the mid-PVN region vs. wild type. These findings suggest that the loss of GABAB signaling may lead to a late developing defect in angiogenesis. The loss of vascularity with defective GABAB signaling suggests that neurovascular relationships in the PVN may be an important locus for understanding disorders of the hypothalamic-pituitary-adrenal axis with potential impact for psychiatric mood disorders along with other comorbid disorders that may be regulated by cells in the PVN.
Keywords: paraventricular nucleus hypothalamic development; GABAB receptors; blood vessel development